The value of new: Elementary school facility age and associated housing price. - Gibson, Huston (My University, 2011)
The purpose of this article is to assess the relationship between elementary school facility age and single-family housing price in the Orlando, Florida metropolitan area. This is a cross-sectional study employing multivariate regression. The model includes facility age as a measure of perceived school quality, along with a series of control variables to assess the relationship between public elementary school facility age and the corresponding housing prices within the associated school attendance zones. This study provides evidence that housing prices are associated with school facility age. The findings show housing prices to be positively correlated with newer and historic school facilities.
Keywords: Elementary school facility age; Single-family housing price; Orlando, Florida; School and housing correlation